Adaptation of evidence‐based guideline recommendations to address urinary incontinence in nursing home residents according to the ADAPTE‐process. Issue 15 (30th May 2018) - Hoedl, Manuela; Schoberer, Daniela; Halfens, Ruud J. G.; Lohrmann, Christa
Abstract : Aims and objectives: To adapt international guideline recommendations for the conservative management of urinary incontinence (UI), defined as any involuntary loss of urine, in Austrian nursing home residents following the ADAPTE‐process. Background: Many international guidelines for managing UI are available. Nevertheless, the international recommendations have not yet been adapted to address the Austrian nursing home context. This crucial adaptation process will enhance the acceptance and applicability of the recommendations as well as encourage adherence among Austrian nurses and nursing home residents. Design: This study is a methodological study based on the ADAPTE‐process, including a systematic search, quality appraisal of the guidelines using theA ppraisal of ClinicalG uidelines forRE search &E valuation II (AGREE II) instrument as well as an external review by means of a Delphi technique. The guidelines had to be topic‐relevant, published within the last 3 years and achieve a rigor of development score of 80% using the AGREE II instrument. Methods: We searched international guideline databases to identify adequate guidelines. Two raters assessed the quality of each guideline, ascertaining that it fulfilled the inclusion criteria using the AGREE II instrument. We translated the identified recommendations into German and externally reviewed for their applicability in the Austrian context. Results: We identified 1, 612 hits in 10 databases. After applying inclusion and exclusion criteria, we assessed five international clinical guidelines for quality using the AGREE II instrument. One clinical guideline fulfilled the inclusion criteria. This clinical guideline contains 116 recommendations, of which 29 were applicable in the Austrian nursing home setting. Conclusion: We identified only one suitable guideline, possibly due to the stringent nature of the inclusion criteria. However, following low‐quality guidelines may result in the use of recommendations that are not based on evidence and, therefore, may lead to suboptimal nursing care and outcomes.